HUBUNGAN ANTARA KEKUATAN OTOT LENGAN DAN KEKUATAN OTOT PERUT TERHADAP KETEPATAN PUKULAN OVERHEAD LOB DALAM PERMAINAN BULUTANGKIS PADA SISWA KELAS VIII MTS NEGERI 3 SUKABUMI TAHUN 2018 - ilham, rio; Bachtiar, Bachtiar; Maulana, Firman (utile: Jurnal Kependidikan, 2018)
This study aims to determine the relationship between arm muscle strength and abdominal muscle strength to the accuracy of the lob overhead punch in badminton game. This research uses quantitative method  with test and measurement technique and processed with multiple correlation statistic analysis. The research sample is the students of Grade VIII MTs Negeri 3 Sukabumi, amounting to 30 people with using random sampling technique. Based on the result of X1 correlation, X2 to Y obtained Fcount is bigger than Ftable, that is Fcount (35,2)> Ftable (2,57) with significance level 0,05. By getting the calculation of RX1X2Y of 0.840 with the category pertained strong and high. And the construction  is simultaneously R2 x 100% = 0.8402 x 100% = 70.5% and the remaining 29.5%. This means that mastery of arm muscle strength and abdominal muscle strength contributes to the accuracy of the lob overhead punch  in badminton games by 70.5%  and the remaining 29.5% by other variables.